Indonesia's Foreign Policy Trajectory Under President Prabowo Subianto: Balancing Assertiveness and Pragmatism in an Evolving Global Order - Setiawan, Asep (Publikasi Indonesia, 2024)
This article examines the potential trajectory of Indonesia's foreign policy under the leadership of President Prabowo Subianto. Drawing on Prabowo's past statements, actions as Defense Minister, and early moves as President, the analysis projects how Indonesia may navigate key regional and global challenges. The research finds that Prabowo is likely to pursue a more assertive and hands-on foreign policy approach compared to his predecessor, while still adhering to Indonesia's foundational